2020
DOI: 10.1177/0194599820957608
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Unilateral Versus Bilateral Injections of Botulinum Toxin for the Treatment of Adductor Spasmodic Dysphonia

Abstract: Objective This study aimed to compare the long-term efficacy, durability, and dose and interval stability between alternating unilateral and bilateral injections of botulinum neurotoxin type A for the treatment of adductor spasmodic dysphonia. Study Design Retrospective cohort study. Setting Academic tertiary medical center. Methods A total of 137 patients (105 alternating unilateral and 32 bilateral injections) who were administered ≥5 injections of botulinum neurotoxin type A were included in this study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
(44 reference statements)
3
7
0
Order By: Relevance
“…These findings suggest that a UL injection regimen may be beneficial specifically for patients with suboptimal outcomes resulting from increased weak and breathy periods and/or swallowing complaints. Findings in the current study are consistent with previous retrospective 4 , 13 and crossover 3 studies which report UL injections provide a shorter length of improved voice compared to BL injections but effectively reduce extended durations of weak and breathy voice.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings suggest that a UL injection regimen may be beneficial specifically for patients with suboptimal outcomes resulting from increased weak and breathy periods and/or swallowing complaints. Findings in the current study are consistent with previous retrospective 4 , 13 and crossover 3 studies which report UL injections provide a shorter length of improved voice compared to BL injections but effectively reduce extended durations of weak and breathy voice.…”
Section: Discussionsupporting
confidence: 91%
“…Findings in the current study are consistent with previous retrospective 4,13 and crossover 3 studies which report UL injections provide a shorter length of improved voice compared to BL injections but effectively reduce extended durations of weak and breathy voice.…”
Section: Effect Of Treatment Approachsupporting
confidence: 91%
See 2 more Smart Citations
“…Unilateral botulinum toxin injections have also been reported as an effective primary treatment for ADLD. Lee et al [97] have observed that both alternating unilateral and bilateral injection regimes demonstrated comparable levels of efficacy, durability, and stability for the treatment of ADLD. The group concluded that alternating unilateral injections could be routinely performed at shorter intervals, with fewer side-effects compared to bilateral injections.…”
Section: Dosing and Laterality Considerations In Adldmentioning
confidence: 99%